Comportamento termodinâmico de cadeias de dímeros - Nascimento, Denise Andrade do (Universidade Federal de São Carlos, 2016)
In this Thesis we propose to describe the thermodynamical properties of dimer chains in a one-dimensional lattice rstly considering q-states of chain orientation in the lattice and secondly by a three states model where the chain orientation is associated with a energy " > 0 or " = 0. For this reason we describe our system by a microcanonical ensemble to get the canonical partition function and through this function obtain the Helmholtz free energy, the entropy, internal energy and pressure. We solved also the problem by adopting the grand canonical ensemble using the transfer matrix method and we get in the thermodynamical limit the equivalence between both ensembles. However the analysis of the thermodynamic properties for systems with nite size is quite relevant since for these nite systems can be found a inequivalence of ensembles. Thereby we performed a detailed study of the Statistical Mechanics for nite particles systems verifying the equivalence o ensembles.
Keywords: Termodinâmica; Mecânica estatística; Dímeros; Rede unidimensional; Matriz de transferência; Thermodynamics; Statistical mechanics; Dimers; One-dimensional lattice; Transfer matrix method; CIENCIAS EXATAS E DA TERRA::FISICA